Origin and Development of the Fiscal Mechanism of Regulation of Investment Processes in the Ukrainian Lands in Princely Times - Viktoriia Rudenko (Науковий вісник Мукачівського державного університету. Серія Економіка, 2020)
The study of the sources and areas of use of the princely treasury and their impact on the development of investment processes in the times of Kyivan Rus becomes particularly relevant, because it allows finding out whether this process was carried out chaotically, or had clear rules and order. The purpose of the study is to consider the peculiarities of the establishment and operation of the tax mechanism for regulating investment processes on the Ukrainian territory in princely times (9th-14th centuries). The specifics of the scientific tasks that make up the subject of research required the use of a set of special methods (empirical and theoretical), the use of which helped to analyse the historical aspects of the development of the fiscal mechanism and its impact on investment during the existence of Kyivan Rus. The study clarified the specifics of the operation of the components of the fiscal mechanism, including revenues and expenditures of the prince's treasury. It is established that in the Kyivan Rus, state treasury revenues were mainly formed from tax sources and came from economic, judicial, military, and commercial activities of the state. It is revealed that the expenses of the princely treasury were directed to meet not only state needs, but also the personal needs of the prince and his wife. It is determined that there were also additional sources of providing for state needs, in particular, in-kind duties. With the arrival of the Mongol-Tatars on Ukrainian lands, the fiscal mechanism changed, because the conquerors introduced their own tax payments, which were collected to meet the needs of the Golden Horde. The budget expenditures of the Mongol-Tatar state did not have a real impact on the investment development of the Ukrainian territories, because they provided exclusively for the needs of the conquering state. The practical value of the study is conditioned by the fact that the historical analysis revealed the mechanism of fiscal influence on investment processes in Kyivan Rus, elements of which can be introduced in modern conditions. This impact was implemented through preferential taxation, the introduction of investment-oriented duties, and the allocation of funds from the princely treasury